SPIRITUALITAS MISTIK SEBAGAI JALAN KESADARAN Tawaran untuk Membangun Teologi Mistik Protestan - Firman Panjaitan (Studia Philosophica et Theologica, 2005)
Mystical theology is a theology of love which is rooted in “in Christ’s life”. The center of mystical experience is Christ himself especially his death on the cross and his resurrection. Mystical theology then will take someone into unity with Christ who was crucified, died and resurrected. This paper intends to dig the meaning of mystical theology which is based on mystical experience of Paul in II Corinthians (12:1-10) and to actualize its understanding to the Indonesian context. I try to make a comparison between Christian experience and the mystical experience of Bima in the tale of Dewa Ruci. Mystical theology is a theology that invites people to “get into life” through the path of suffering. It is not a picture about life that loves suffering, but that of a “love road”. By following the path of suffering, someone is brought to life.